Optimizing Employee Innovation through Training: A Social Learning Theory Perspective with Self-Efficacy as a Mediator - Firdaus, Firdaus; Mursanto, Mursanto; Lusiana, Herlina (Journal of Economics and Management Scienties, 2025)
This research examines how employee training influences innovative behavior, with self-efficacy serving as a mediating factor, and is grounded in Social Learning Theory. A quantitative approach was used to analyze data from 320 PT Cakra Kencana Lestari employees using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that training significantly impacts innovation, both directly and indirectly, by enhancing self-efficacy. These findings contribute to the literature by empirically validating the psychological mechanism through which training fosters innovative behavior. The study underscores the strategic importance of integrating self-efficacy development into training design to maximize innovation outcomes. Practical implications suggest that organizations adopt learning interventions that build technical skills and empower employees psychologically. Future research should explore other mediating or moderating factors, such as leadership, organizational support, or motivation, in various organizational contexts.